Antibody reactivity with new antigens revealed in multi‐transgenic triple knockout pigs may cause early loss of pig kidneys in baboons. (9th September 2020) - Ariyoshi, Yuichi; Takeuchi, Kazuhiro; Pomposelli, Thomas; Ekanayake‐Alper, Dilrukshi K.; Shimizu, Akira; Boyd, Lennan; Estime, Ermance; Ohta, Mayu; Asfour, Arsenoi; Scott Arn, J.; Ayares, David; Lorber, Marc; et al.
Abstract: Background: Recent advances in gene editing technology have enabled the production of multi‐knockout (KO) and transgenic pigs in order to overcome immunologic barriers in xenotransplantation (XTx). However, the genetic manipulations required to produce these changes may have the unintended consequence of producing or revealing neoantigens reactive with natural antibodies present in baboons. In this study, we examined whether the neoantigens that develop in multi‐transgenic (mTg) GalT, Cytidine monophospho‐N‐acetylneuraminic acid hydroxylase (CMAH), β‐1, 4‐N‐acetyl‐galactosaminyl transferase 2 (B4) KO pigs can cause rejection of xenografts in baboons. Methods: Five baboons that had <35% cytotoxicity against GalT‐KO peripheral blood mononuclear cells (PBMCs) in a pre‐screening assay received pig kidneys and vascularized thymic grafts (VT + K) from multi‐transgenic hCD47, human thrombomodulin (hTBM), human endothelial protein C receptor (EPCR) with/without hCD46 and hCD55 with GalT‐KO/NeuGC‐KO/B4‐KO (mTg Tri‐KO) swine. In order to further examine the effects of anti‐donor non‐Gal natural antibody (nAb), anti‐pig preformed IgM and IgG nAb binding against the GalT‐KO PBMCs was compared with the donor‐type PBMCs using donor pretransplant sera as well as 5 additional naïve baboon sera by flow cytometric analysis. Results: Five baboons that received VT + K grafts had stable renal function in the first 11 days (serum creatinine < 1.5 mg/dL). Two of the five baboons had higher binding of preformed IgG to mTg Tri‐KO PBMCs than to GalT‐KO PBMCs (mTg Tri‐KO > GalT‐KO), and they rejected their grafts at POD 20. In contrast, the other three baboons demonstrated either mTg Tri‐KO = GalT‐KO or mTg Tri‐KO < GalT‐KO, and they maintained renal function 43, 52, and 154 days without rejection. Among 10 baboon sera, two had less antibody binding against PBMCs that were syngeneic to the mTg Tri‐KO than against GalT‐KO PBMCs (mTg Tri‐KO < GalT‐KO); three had similar binding to mTg Tri‐KO and GalT‐KO PBMCs (mTg Tri‐KO = GalT‐KO); and five had higher binding to m Tg Tri‐KO than to GalT‐KO PBMCs (mTg Tri‐KO > GalT‐KO). Conclusions: These data suggest that neoantigens associated with mTg Tri‐KO promote acute xenograft rejection in a pig‐to‐baboon VT + K XTx model. The screening assays may be useful to select "safe" recipients to receive mTg Tri‐KO kidneys.